Kwestie kobiece w założeniach programowych i praktyce politycznej niemieckich Zielonych w latach 1980-2005 = The women's issues in program principles and political practices of Germany's Greens in 1980-2005 - Trajman, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the analysis of program and electoral demands of The Greens pertaining to the women's issues since the establishment of the party in 1980 till the end of the federal government held jointly with the SPD in 2005. The objective of the article was to determine whether the political grouping that should be in its essence an "anti-party", existing in the opposition to the traditional groups not just because of the political demands but also the way they operated, was able to stand by their demands and accomplish them, acting in the red-green coalition of two governments of Gerhard Schroder.
Keywords: kwestie kobiece; niemieccy Zieloni; czerwono-zielona koalicja 1998-2005; women's issues; The Greens in Germany; red-green coalition 1998-2005